Investigation of Partial Oxidation of Methane at Different Reaction Parameters by Adding Ni to CeO2 and ZrO2 Supported Cordierite Monolith Catalyst - Bayraktar, Ilke Ilicak; Figen, Halit Eren (MDPI, 2024)
The climate crisis, driven by increasing CO2 levels in the atmosphere, has heightened the need for new, environmentally friendly energy sources. Hydrogen gas, which can meet our energy needs, has become a particularly intriguing topic. This study investigated the partial oxidation reaction of methane with cordierite monolith catalysts. The Ni-coated catalysts were supported with gamma-Al2O3, CeO2, ZrO2, and CeO2-ZrO2. The catalysts were tested at temperatures of 750, 800, and 850 degrees C with different flow rates and methane feed concentrations (2%, 5%, and 10%). It was demonstrated that catalyst activity varies depending on these parameters. It has been found that high gas hourly space velocity (GHSV) and CH4 feed rates decrease catalyst activity. The obtained reaction results indicated that the optimal reaction parameters were 800 degrees C, a GHSV of 1 x 10(4) h(-1), and a CH4 feed concentration of 2%. By optimizing these parameters, catalysts with high CH4 conversion and selectivity for H-2 and CO were achieved. The prepared catalysts were characterized using scanning electron microscopy with energy dispersive X-ray analysis (SEM-EDX), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), and temperature-programmed reduction (TPR).
Keywords: catalytic partial oxidation; methane; monolith; hydrogen; supported catalyst; HYDROGEN-PRODUCTION; SYNGAS PRODUCTION; DECOMPOSITION; OPTIMIZATION; Engineering